Exercise-Induced Asthma: Challenges of Exercise and Management - Serly, Vicennia; Basyar, Masrul; Herman, Deddy (Eduvest - Journal of Universal Studies, 2025)
Exercise-Induced Asthma (EIA), also known as exercise-induced bronchospasm (EIB), is a condition in which the airways become blocked after exercise. Although exercise can cause asthma attacks, a lack of exercise can make asthma worse. Apart from taking medication, exercise can help control asthma attacks, and help improve the quality of life of the asthmatic population. Exercise can be done by people with mild to moderate degrees of airway obstruction, just like healthy people. Swimming, walking, cycling, playing ball and aerobics are good sports for asthma patients. Exercise-Induced Asthma (EIA) can also prevent asthma patients from exercising and affect their quality of life. The diagnosis of EIA is based on symptoms and spirometry or bronchial provocation tests. Nonpharmacological approaches, including avoidance of precipitating factors, are essential. SABA before exercise is also widely used and recommended as first-line therapy. Inhaled corticosteroids are recommended when asthma control is less than optimal. Leukotriene receptor antagonists (LTRA) and mast cell stabilizing agents (MCSA) are potential options.